2017
DOI: 10.1111/aos.13460
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of big bubble formation in deep anterior lamellar keratoplasty by the big bubble technique: in vitro studies

Abstract: The consistent pattern of passage of air is indicative of the architecture and microanatomy of the corneal stroma where collagen lamellae are orthogonally arranged centrally and as a circular annulus at the periphery. The novel peripheral fenestrations explain the peripheral commencement of a type-2BB and the escape of air into the anterior chamber during DALK.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
28
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(32 citation statements)
references
References 25 publications
(29 reference statements)
4
28
0
Order By: Relevance
“…In the BB procedure, air is injected into the recipient stroma through a trephine cut of desired diameter (usually 7.5–8 mm). Injected air follows a defined and reproducible path[ 49 ] to reach the PDL plane, to produce a Type-1 BB. This is the most common type, occurring in approximately 80% of patients.…”
Section: Deep Anterior Lamellar Keratoplastymentioning
confidence: 99%
“…In the BB procedure, air is injected into the recipient stroma through a trephine cut of desired diameter (usually 7.5–8 mm). Injected air follows a defined and reproducible path[ 49 ] to reach the PDL plane, to produce a Type-1 BB. This is the most common type, occurring in approximately 80% of patients.…”
Section: Deep Anterior Lamellar Keratoplastymentioning
confidence: 99%
“…The response is different between injection of air and injection of viscoelastic. Injected air follows a consistent path through spaces between lamellae (presumably around keratocytes) to reach the plane between the PDL (impervious to air) and deep stroma, separating the two in a type 1 BB, or through peripheral fenestrations in PDL to access the plane between PDL and DM to form a type 2 BB 11. No IBB occurred with air injection.…”
Section: Discussionmentioning
confidence: 95%
“…No IBB occurred with air injection. Though air takes a consistent path intrastromally11 a BB does not always result in vivo possibly due to the altered collagen content of scarred or keratoconus corneas. The path traversed by air appears to be too narrow for the viscoelastic used.…”
Section: Discussionmentioning
confidence: 99%
“…The volume of air required to achieve the critical tissue pressure depends on the escape of air through the trabecular meshwork or through distinct peripheral holes in the stroma, during injection. [7][8][9] This confounder was eliminated by the use of the clamp, which prevented any escape of air, thus giving us an accurate measure of the mean tissue pressure required to create a BB overcoming tissue resistance, which was 96.25 +/ − 21.61 kpa. It has been recently demonstrated that air injected in the corneal stroma follows a consistent path regardless of the location, direction of bevel, and depth of the needle tip in the stroma.…”
Section: Discussionmentioning
confidence: 99%
“…It has been recently demonstrated that air injected in the corneal stroma follows a consistent path regardless of the location, direction of bevel, and depth of the needle tip in the stroma. 9 Once a type-1 BB was created, the intrabubble pressure was ascertained by advancing the needle into the cavity of the BB. This measured 10.16 +/ − 3.65 kpa.…”
Section: Discussionmentioning
confidence: 99%